ผลของการเคลือบฟันกรามแท้ซี่ที่สองที่ขึ้นเพียงบางส่วนด้วยกลาสไอโอโนเมอร์ต่อเชื้อมิวแทนส์ สเตรปโตคอคไค และฟลูออไรด์ในแผ่นคราบจุลินทรีย์ - ณัฐฐา ไร่ทิม (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Objectives : To determine whether application of glasss ionomer sealant could effect the fluoride and mutans streptococci levels in dental plaque of newly erupted permanent molar. Methodology : This prospective study included 45 high-caries-risk children, aged 10 to 13 years, who had a partially erupted second permanent molar. The erupting molar was sealed with glass ionomer sealant. Dental plaque samples were collected before and 7 days, 14 days, and 28 days after sealant application. The fluoride and mutans streptococci levels were measured by the modified microdiffusion technique and by the chair-site strip tests, respectively. Results : Seven days after placement of glass ionomer, a statistically significant increase in the fluoride level of dental plaque was found (p < 0.0001), as well as a reduction of mutans strepetococci count (p < 0.0001). However, such changes were gradually declined thereafter. Conclusion : It is concluded that sealing on partially erupted second molars with glass ionomer has a significant but only short - term effect on the fluoride and mutans streptococci levels in dental plaque.